(untitled) (Olhar de Professor, 2023)
The exile of argentine pedagogues in Mexico brought with it contributions in more than one area of pedagogical intervention and conceptual developments in education. Azucena Rodríguez Ousset, Justa Ezpeleta and Alfredo Furlan, argenmex exiles from Córdoba, Argentina, joined different institutions of higher education and research during the 1970s. In this article, from the perspective of Gerbaudo (2016) on the configuration of an archive and Granja (1998) on the conformation of ordering theoretical lines in concrete social and political contexts, contributions of these three pedagogues were explored around four axes: Pedagogy: transmission and intervention; school and pedagogy; school, pedagogical management and discipline; teaching.